Identification of NLE1/CDK1 axis as key regulator in the development and progression of non-small cell lung cancer - Xu, Pei; Wang, Lei; Mo, Bin; Xie, Xiao; Hu, Rui; Jiang, Lianyong; Hu, Fengqing; Ding, Fangbao; Xiao, Haibo (Frontiers in Oncology, 2023)
Non-small cell lung cancer (NSCLC) is the most common pathological type of lung cancer, which is a severer threaten to human health because of its extremely high morbidity and mortality. In this study, the role of Notchless homolog 1 (NLE1) in the development of NSCLC was investigated and the underlying mechanism was explored. The outcomes showed that NLE1 expression is significantly higher in tumor tissues than normal tissues, and is correlated with the pathological stage. The regulation of NSCLC development by NLE1 was also visualized by the in vitro and in vivo loss-of-function studies, which indicated the inhibition of cell growth and migration, as well as enhancement of cell apoptosis on condition of NLE1 knockdown. As for the mechanism, it was demonstrated that NLE1 may execute its tumor-regulating function through activating E2F1-mediated transcription of CDK1, and PI3K/Akt signaling pathway was also supposed as a downstream of NLE1 in the regulation of NSCLC. Both CDK1 overexpression and treatment of Akt pathway activator could reverse the NLE1 knockdown induced NSCLC inhibition to some extent. In conclusion, this study identified NLE1 as a novel tumor promotor in the development and progression of NSCLC, which may be a potential therapeutic target in the treatment of NSCLC.